Preliminary Survey of Industrial Perception On Using Immobillised Microalgae, Botryococcus sp. For Wastewater Bioremediation - Apandi, Najeeha (Progress in Engineering Application and Technology, 2021)
The water pollution is a serious threat all over the world in the light of limited fresh water availability and increasing generation of wastewater being discharged prior to the environment. This study is to investigate the perception and to analyse the knowledge of people from different industries on the usage of microalgae Botryococcus sp. for wastewater bioremediation.There are various manufacturing industries in Malaysia which use high amount of water. Palm oil industries, textile industry, fibreboard industry, automotive industry and food industry were selected for this survey. Based on the data, food factory industry has more knowledge compare with others industry. However, it is pleasing to note that the industries are willing to contribute to this study that would reduce the risk of contamination of wastewater. It is therefore recommended that the insdustrial should adopt the concept of wastewater bioremediation to emphasize institutional effectiveness and promote awareness campaign for better wastewater management.